Earthwork Planning and Visualisation of Time-Location Information in Road Construction Projects - Shah, R. K. (Journal of Advanced College of Engineering and Management, 2016)
Accurate information of locations from visual aspect is vital for efficient resource planning and managing the workspace conflicts in the earthwork operations, which are missing in the existing linear schedules. Hence, the construction managers have to depend on the subjective decisions and intangible imagining for resources allocation, workspace conflicts and location-based progress monitoring in the earthwork projects. This has caused uncertainties in planning and scheduling of earthworks, and consequently delays and cost overruns of the projects. To overcome these issues, a framework of computer based prototype model was developed using the theory of location-based planning. This paper focuses on the case study experiments to demonstrate the functions of the model, which includes automatic generation of location-based earthwork schedules and visualisation of cut-fill locations on a weekly basis. The experiment results confirmed the model’s capability in identifying precise weekly locations of cut-fill and also visualising the time-space conflicts at the earthwork projects. Hence, the paper concludes that the model is a useful decision supporting tool to improve site productivity and reduce production cost of earthworks in the construction projects like roads and railways. Journal of Advanced College of Engineering and Management, Vol. 1, 2015, pp. 75-84